Menimbang Moralitas dan Rasionalitas: Studi Kritis Fenomena Tren Nikah Muda dan Penundaan Perkawinan melalui Perspektif Maqashid Syariah dan Teori Tindakan Sosial Max Weber - Rafliyanto (UIN Sunan Kalijaga Yogyakarta, 2025)
This study aims to analyze the phenomenon of early marriage and marriage postponement trends in Indonesia from the perspectives of maqashid sharia and social aspects, with a focus on social implications and the impact on public policy. Early marriage is often promoted as a moral solution to avoid zina, while marriage postponement is more commonly chosen by the younger generation who prioritize education, career, and financial stability. However, both phenomena pose challenges related to the mental, economic, and social readiness of the individuals involved, which can potentially affect the well-being of families and society. This research adopts a normative-sociological approach with Max Weber’s theory of social action to understand the motivations behind the decisions to marry early or postpone marriage. Data was obtained through semi-structured interviews with young couples and young people who chose to delay marriage. The results of the study show that, although there are good intentions behind the promotion of early marriage, marriages carried out without adequate readiness can lead to social and economic problems, and contradict maqashid sharia, which emphasizes the importance of stability and well-being in marriage. On the other hand, postponing marriage provides advantages in terms of financial and psychological readiness, but also brings negative impacts, such as a decline in birth rates and changes in social structure. The limitations of this study lie in its narrow geographical scope and its focus on the perspectives of Islamic law and sociology. Penelitian ini mengkaji fenomena ajakan menikah muda dan tren penundaan perkawinan di Indonesia dengan menganalisis perspektif sosial, budaya, dan hukum Islam. Nikah muda sering kali dipromosikan sebagai solusi masalah moral dan jalur untuk membangun keluarga harmonis, didorong oleh narasi media sosial dan dorongan agama. Sebaliknya, penundaan perkawinan semakin umum terjadi pada generasi muda yang memprioritaskan pendidikan, karier, dan stabilitas finansial. Penelitian ini menggunakan pendekatan Normatif-Sosiologis teori Tindakan sosial Max Webber dan pendekatan Maqasid Syariah dengan metode kajian pustaka dan wawancara semi-terstruktur untuk menganalisis motivasi mendasar dan dampak sosial dari kedua tren ini. Hasil penelitian menunjukkan implikasi signifikan terhadap kesejahteraan individu, struktur keluarga, dan kebijakan publik, dengan menekankan pentingnya kesiapan dan keseimbangan dalam pengambilan keputusan pernikahan. Studi ini juga menyoroti relevansi maqashid syariah dalam menjembatani fenomena ini, serta memberikan rekomendasi praktis melalui pendidikan, kebijakan, dan pemberdayaan komunitas.